Decoding microbial genomes to understand their functional roles in human complex diseases. Issue 2 (29th March 2022) - Wang, Yifeng; Dong, Quanbin; Hu, Shixian; Zou, Huayiyang; Wu, Tingting; Shi, Jing; Zhang, Haifeng; Sheng, Yanhui; Sun, Wei; Kong, Xiangqing; Chen, Lianmin
Abstract: Complex diseases such as cardiovascular disease (CVD), obesity, inflammatory bowel disease (IBD), kidney disease, type 2 diabetes (T2D), and cancer have become a major burden to public health and affect more than 20% of the population worldwide. The etiology of complex diseases is not yet clear, but they are traditionally thought to be caused by genetics and environmental factors (e.g., dietary habits), and by their interactions. Besides this, increasing pieces of evidence now highlight that the intestinal microbiota may contribute substantially to the health and disease of the human host via their metabolic molecules. Therefore, decoding the microbial genomes has been an important strategy to shed light on their functional potential. In this review, we summarize the roles of the gut microbiome in complex diseases from its functional perspective. We further introduce artificial tools in decoding microbial genomes to profile their functionalities. Finally, state‐of‐the‐art techniques have been highlighted which may contribute to a mechanistic understanding of the gut microbiome in human complex diseases and promote the development of the gut microbiome‐based personalized medicine. Abstract : Functional roles of the gut microbiome in human health and disease. Commonly used tools in decoding microbial functionalities. State of the art techniques in validating microbial functionalities. Highlights: Functional roles of the gut microbiome in human health and disease. Commonly used tools in decoding microbial functionalities. State of the art techniques in validating microbial functionalities.